2020
DOI: 10.1016/j.heliyon.2020.e04586
|View full text |Cite
|
Sign up to set email alerts
|

Psychoeducational Group Therapy for sexual function and marital satisfaction in Iranian couples with sexual dysfunction disorder

Abstract: Background Having sexual relations plays a very important role in the success and scope of procreation. Understanding sexual function can lead to sexual satisfaction and ultimately to marital satisfaction and reconciliation of spouses. Objective The aim of this study was to evaluate the effectiveness of a psychoeducational programme on sexual function and marital satisfaction of Iranian couples. Materials and methods This is a semi-experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…The positive effect of couple therapy education on marital satisfaction of couples was reported in some studies ( 33 – 36 ).…”
Section: Resultsmentioning
confidence: 74%
“…The positive effect of couple therapy education on marital satisfaction of couples was reported in some studies ( 33 – 36 ).…”
Section: Resultsmentioning
confidence: 74%
“…Sexual problems are one of them. Recently emerging literature has revealed that sexual problems negatively affect marriage satisfaction in both healthy women and healthy men all over the world [24][25][26]. Also, it affects the marriage satisfaction of people who has a neurological disorder such as MS [5] and Parkinson's disease [27].…”
Section: Discussionmentioning
confidence: 99%
“…The results of Tahan et al . 's showed psycho-educational group consulting helps to increase sexual functioning and marital satisfaction of married couples[ 25 ] and the study of Bostani et al . also showed Information about sexual health is one of the essential needs of young couples.…”
Section: Discussionmentioning
confidence: 99%